2002
DOI: 10.1007/s11745-002-0975-2
|View full text |Cite
|
Sign up to set email alerts
|

Destabilizing effects of fructose‐1,6‐bisphosphate on membrane bilayers

Abstract: Fructose-1,6-bisphosphate (FBP) is a high-energy glycolytic intermediate that decreases the effects of ischemia; it has been used successfully in organ perfusion and preservation. How the cells utilize external FBP to increase energy production and the mechanism by which the molecule crosses the membrane bilayer are unclear. This study examined the effects ofFBP on membrane bilayer permeability, membrane fluidity, phospholipid packing, and membrane potential to determine how FBP crosses the membrane bilayer. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Another study demonstrated that cells and tissues treated with labelled [C 13 ]FBP produce [C 13 ]lactate, which indicates that exogenously given FBP can participate in the glycolytic pathway to reestablish ATP pool inside the cells [28]. One hypothesis is that FBP could briefly interact with calcium that stabilizes bilayer lipid membrane, leading to an increase in membrane fluidity that would allow FBP to cross it through passive diffusion [29]. Further, the permeability of FBP through a dicarboxylate transporter was reported, although only the linear form of FBP, a small fraction of total FBP, can use this system [30].…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that cells and tissues treated with labelled [C 13 ]FBP produce [C 13 ]lactate, which indicates that exogenously given FBP can participate in the glycolytic pathway to reestablish ATP pool inside the cells [28]. One hypothesis is that FBP could briefly interact with calcium that stabilizes bilayer lipid membrane, leading to an increase in membrane fluidity that would allow FBP to cross it through passive diffusion [29]. Further, the permeability of FBP through a dicarboxylate transporter was reported, although only the linear form of FBP, a small fraction of total FBP, can use this system [30].…”
Section: Discussionmentioning
confidence: 99%
“…Fru-1,6-P 2 has been reported to enter myocytes and large unilamellar vesicles (28,29), although the mechanism is controversial. Instead of using Fru-1,6-P 2 , we used the cell-permeable analog 2,5-AM, which enters cells and is phosphorylated to yield 2,5-AM-ol bisphosphate (30), which accumulates in the cytosol because it is not metabolized.…”
Section: Volume 286 • Number 23 • June 10 2011mentioning
confidence: 99%
“…Thus, during hemorrhagic shock, all energy-dependent processes including membrane transport are compromised severely resulting in an osmotic imbalance leading to cellular edema. Replenishing ATP by means of resuscitation in hemorrhagic shock, however, has been ineffective due both to its inability to pass the cell membrane in large quantities as well as its short half-life in circulation [25–31]. Administration of glutamine (a precursor of ATP), lipid encapsulated ATP, pyruvate, and crocetin have been effective in restoring energy and decreasing cellular damage after hemorrhagic shock in animal models [5,3234].…”
Section: Discussionmentioning
confidence: 99%